2011
DOI: 10.1039/c1py00073j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in sunlight induced polymerization: role of new photoinitiating systems based on the silyl radical chemistry

Abstract: Silyl radical chemistry opens new opportunities for photoinitiating systems for sunlight polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 61 publications
(22 reference statements)
0
73
0
2
Order By: Relevance
“…However, photopolymerization reactions under low intensity visible light irradiation conditions were rather rare and challenging before 2011. As some reviews regarding PISs have been published [1][2][3]5,7,8,18,25,[95][96][97][98][99][100], this review mainly describes the development of new PISs applicable to visible lights in the period of 2011 to early 2014 and is also an opportunity to gather the relative performance of the PISs we have recently designed, in order to propose a "one pot" comparison to the readers. Photoinitiator catalysts [19] and photosensitive systems in controlled polymerization reactions [20][21][22][23][24] have been reviewed recently and will be considered in Section 6.…”
Section: Introductionmentioning
confidence: 99%
“…However, photopolymerization reactions under low intensity visible light irradiation conditions were rather rare and challenging before 2011. As some reviews regarding PISs have been published [1][2][3]5,7,8,18,25,[95][96][97][98][99][100], this review mainly describes the development of new PISs applicable to visible lights in the period of 2011 to early 2014 and is also an opportunity to gather the relative performance of the PISs we have recently designed, in order to propose a "one pot" comparison to the readers. Photoinitiator catalysts [19] and photosensitive systems in controlled polymerization reactions [20][21][22][23][24] have been reviewed recently and will be considered in Section 6.…”
Section: Introductionmentioning
confidence: 99%
“…[70][71][72] Photoinitiation with disilanes having an Si-Si bond is also possible through electron transfer and Si-Si bond dissociation. It has been found that silane compounds can be efficiently employed as co-initiator to initiate photopolymerization in the presence of photoinitiators.…”
Section: Methodsmentioning
confidence: 99%
“…Following these strategies, elegant green systems have been proposed [318][319][320][321][322][323][324][325] such as the polymerization of renewable epoxy monomers under sunlight [319]. This is contributing to make photolatent onium salts more and more attractive.…”
Section: Page 29 Of 163mentioning
confidence: 99%